1989
DOI: 10.1161/01.cir.79.5.1068
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective disposition and pharmacologic activity of propafenone enantiomers.

Abstract: Propafenone is an antiarrhythmic drug that produces a variable degree of P3-blockade in humans and is administered as a racemate. To examine the relative contribution of the individual enantiomers to pharmacologic effects seen during treatment with propafenone, we assessed the steady-state plasma concentrations of (+)-S-propafenone and (-)-R-propafenone in seven patients who were on long-term oral therapy, and we evaluated the electrophysiologic and p3-blocking properties of both enantiomers in vitro. The meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(42 citation statements)
references
References 33 publications
3
39
0
Order By: Relevance
“…Irrespective of dextro-or laevorotatory properties, resolved enantiomers with (S)-configuration, as determined chromatographically and by CD-spectroscopy, exerted considerably higher fi-adrenoceptor affinity than their corresponding (R)-enantiomers. A similar pattern of stereoselectivity has recently been reported for the binding of propafenone to human lymphocyte JJ-adrenoceptors (Kroemer et al, 1989). In the present experiments, enantiomeric affinity ratios of 1.2-1.8 log units were obtained.…”
Section: Discussionsupporting
confidence: 90%
“…Irrespective of dextro-or laevorotatory properties, resolved enantiomers with (S)-configuration, as determined chromatographically and by CD-spectroscopy, exerted considerably higher fi-adrenoceptor affinity than their corresponding (R)-enantiomers. A similar pattern of stereoselectivity has recently been reported for the binding of propafenone to human lymphocyte JJ-adrenoceptors (Kroemer et al, 1989). In the present experiments, enantiomeric affinity ratios of 1.2-1.8 log units were obtained.…”
Section: Discussionsupporting
confidence: 90%
“…This lipophilic, high-clearance drug is subject to variable first-pass metabolism and nonlinear pharmacokinetics (Siddoway et al, 1987;Capucci et al, 1990). Its enantiomers have equal sodium channel blocking activity (the primary effect), but S-propafenone is 100-fold more potent as a ␤-blocker (Kroemer et al, 1989a). Propafenone is metabolized via CYP2D6 to 5-hydroxypropafenone, which has sodium channel blocking activity similar to that of the racemic parent drug but less ␤-blockade (Kroemer et al, 1989b), and also by CYP1A2 and 3A4 to N-desalkylpropafenone (some, but less, activity) (Botsch et al, 1993).…”
Section: Antipsychoticsmentioning
confidence: 99%
“…The propafenone/ 5-hydroxypropafenone ratio correlates with the debrisoquine metabolic ratio . PMs have 3-to 7-fold higher propafenone AUCs at steady state than EMs and produce very low or negligible concentrations of 5-hydroxypropafenone (Siddoway et al, 1987;Kroemer et al, 1989a;Lee et al, 1990;Dilger et al, 1999;Labbe et al, 2000). CYP2D6 status is generally thought to matter little for antiarrhythmic effect (Siddoway et al, 1987;Labbe et al, 2000), although some studies have suggested greater efficacy in those with reduced CYP2D6 activity (Jazwinska-Tamawska et al, 2001;Cai et al, 2002).…”
Section: Antipsychoticsmentioning
confidence: 99%
“…On the basis of the conceptual framework discussed in Theoretical Considerations of Determining In Vivo Metabolite Exposure, this was ascribed to either a low CL f and/ or a high CL m for the metabolite. For instance, low circulating concentrations of N-desalkyl metabolites of azimilide (Riley et al, 2005), elzasonan (Kamel et al, 2010), imatinib (Gschwind et al, 2005), itraconazole (Isoherranen et al, 2004), olanzapine (Kassahun et al, 1997), propafenone (Kroemer et al, 1989), and repaglinide (van Heiningen et al, 1999) can be attributed to the relatively minor contribution of N-dealkylation to the overall clearance of these drugs. On the other hand, low circulating concentrations of mchlorophenylpiperazine (Fig.…”
Section: Secondary or Primary Amines As Metabolitesmentioning
confidence: 99%